PIC microcontroller demystified - Wan Norhisyam Abd. Rashid; Nik Mohd Zaitul Akmal Mustapha (Penerbit Universiti Malaysia Pahang, 2014)
This book is a must have book for any students, electronics enthusiasts and engineers who need a quick access of information about PIC microcontrollers in order to help them in designing an electronic embedded system